2015
DOI: 10.1021/jo502135d
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of Quinoxalin-2-ones When Exposed to Enamines Generated in Situ from Ketones and Ammonium Acetate: Method for the Synthesis of 1-(Pyrrolyl)benzimidazolones

Abstract: The reaction of 3-benzoylquinoxalin-2(1H)-ones with enamines (generated in situ from ammonium acetate and the corresponding methylaryl(hetaryl)ketones) proceeds smoothly to give the corresponding substituted 1-(pyrrolyl)benzimidazolone derivatives in moderate yields through the novel rearrangement of 3-benzoylquinoxalin-2(1H)-ones involving a dual cleavage of the C3═N4 and C2-C3 bonds under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In our previous work, the reactions of 3-aroylquinoxalin-2­(1 H )-ones and their 5- and 7-aza-analogues, namely, 3-benzoylpyrido-[3,2- b ]­pyrazin-2­(1 H )-one and 3-benzoylpyrido­[3,4- b ]-pyrazin-2­(1 H )-one, with enamines in acetic acid, were found to give variously substituted 1-[pyrrol-4­(and 5)-yl]-benzimidazol-2­(3 H )-ones through the quinoxalinone–benzimidazolone rearrangement. In these examples, commercially available enamines were used, namely, methyl- and ethyl-3-aminocrotonates (a) and enamines generated in situ in the reactions of variously substituted acetophenone derivatives with ammonium acetate (b) . Assuming that the enamine triatomic moiety is an integral part of amidines and imino esters and can be easily generated by the interaction of amines with nitriles with an active methylene group, in this paper, we present the results of studies of reactions proceeding in a multicomponent system containing aroylquinoxalinones, malononitrile, and various nucleophilic reagents (amines and alcohols) in the presence of acetic acid (c) (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, the reactions of 3-aroylquinoxalin-2­(1 H )-ones and their 5- and 7-aza-analogues, namely, 3-benzoylpyrido-[3,2- b ]­pyrazin-2­(1 H )-one and 3-benzoylpyrido­[3,4- b ]-pyrazin-2­(1 H )-one, with enamines in acetic acid, were found to give variously substituted 1-[pyrrol-4­(and 5)-yl]-benzimidazol-2­(3 H )-ones through the quinoxalinone–benzimidazolone rearrangement. In these examples, commercially available enamines were used, namely, methyl- and ethyl-3-aminocrotonates (a) and enamines generated in situ in the reactions of variously substituted acetophenone derivatives with ammonium acetate (b) . Assuming that the enamine triatomic moiety is an integral part of amidines and imino esters and can be easily generated by the interaction of amines with nitriles with an active methylene group, in this paper, we present the results of studies of reactions proceeding in a multicomponent system containing aroylquinoxalinones, malononitrile, and various nucleophilic reagents (amines and alcohols) in the presence of acetic acid (c) (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2000, we discovered the acid‐catalyzed rearrangement of 3‐aroylquinoxalin‐2‐ones into 2‐(benzimidazol‐2‐yl)quinoxalines when exposed to 1,2‐benzenediamines [8] . In the last two decades, we have published a series of works on the rearrangement of quinoxalin‐2‐ones via the proposed spiro‐quinoxalinone [9] intermediates ( A ) into 2‐hetarylbenzimidazoles [9a–h] ( B , Type I) as well as 1‐hetarylbenzimidazolones in cases of enamine nucleophiles ( C , Type II, Scheme 1), [9i–k] thus opening a simple way to access various 2‐hetarylbenzimidazoles and 1‐hetarylbenzimidazolones according to the S N (ANRORC) mechanism (i. e., via sequential steps of addition of nucleophile, ring‐opening and ring‐closing) [10] . It was shown that the type of rearrangement may depend on the fact if tautomerizable hydrogen is available or not in the spiro‐forming ring within A .…”
Section: Methodsmentioning
confidence: 99%
“…Further protonation of nD at amine NH with AcOH may lead to the ring‐opening cation nDo + , which is however 36.3 kcal/mol endergonic with respect to reactant 1 Q , clearly disfavoring the Type I rearrangement [10] . In contrast, direct amine shift of spiro‐intermediate nD + via isocyanate cation [11] like transition structure nTSE + is kinetically about 10 kcal/mol more favorable to form the five‐membered‐ring nE + , which after N ‐protonation with AcO − eventually leads to the observed [9j] N ‐(pyrrol‐3‐yl)benzimidazol‐2‐one ( 2 bn ) product.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This chemistry is not limited to the quinoxalin-2(1H)-ones and the 5-and 7-aza-quinoxalin-2(1H)-ones, namely 3-benzoylpyrido [3,2-b]pyrazin-2(1H)-one 95a and 3-benzoylpyrido [3,4-b] pyrazin-2(1H)-one 95d subjected to the rearrangement with the formation easily separable regioisomeric products 162/163 and 164/165 with overall quantitative yields (Scheme 68). 129 In comparison with the existing methods, the present approach offers the following advantages: (i) it proceeds faster and affords good to excellent yields under mild conditions with no additional activation modes such as microwave irradiation, (ii) it is very cost-effective and uses the inexpensive easily and commercially available reagents, and (iii) it is applicable to a broader range of substrates, including 3-aroyl(alkanoyl)quinoxalin-2(1H)-ones, 3-benzoylpyrido[3,2-b]pyrazin-2(1H)-one and 3-benzoylpyrido [3,4-b]pyrazin-2(1H)-one and various enamines.…”
Section: Synthesis Of 2-(benzimidazol-2-yl) Quinolinesmentioning
confidence: 99%